2022
DOI: 10.1002/ijc.34252
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of plasma metabolites with persistent fatigue among colorectal cancer survivors up to 2 years after treatment

Abstract: The underlying biological mechanisms causing persistent fatigue complaints after colorectal cancer treatment need further investigation. We investigated longitudinal associations of circulating concentrations of 138 metabolites with total fatigue and subdomains of fatigue between 6 weeks and 2 years after colorectal cancer treatment. Among stage I-III colorectal cancer survivors (n = 252), blood samples were obtained at 6 weeks, and 6, 12 and 24 months posttreatment. Total fatigue and fatigue subdomains were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…It is possible that this type of multimodal approach could be responsible for the observed reduction in fatigue because physical activity and cognitive behavioral therapy interventions have been shown to effectively reduce fatigue in CRC patients [ 42 , 43 , 44 ]. However, it is just as possible that the same fatigue improvement could have been observed without in-patient rehabilitation because some studies showed that fatigue levels could reduce after treatment, even without any intervention or medication, possibly due to the gradual reduction in inflammation caused by treatment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this type of multimodal approach could be responsible for the observed reduction in fatigue because physical activity and cognitive behavioral therapy interventions have been shown to effectively reduce fatigue in CRC patients [ 42 , 43 , 44 ]. However, it is just as possible that the same fatigue improvement could have been observed without in-patient rehabilitation because some studies showed that fatigue levels could reduce after treatment, even without any intervention or medication, possibly due to the gradual reduction in inflammation caused by treatment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scale consists of 22 numeric rating scales, assessing fatigue across four subdomains: behavioral (6 items), affective (5 items), sensory (5 items), and cognitive (6 items). Fatigue severity is described using a 10-point numeric scale: mild (1, 2), moderate (3)(4)(5), and severe (6)(7)(8)(9). Assessments were made before treatment (baseline, T0), after 1 week of treatment (T1), after 2 weeks of treatment (T2), after 3 weeks of treatment (end of treatment, T3), and after 6 weeks of treatment (end of follow-up, T4).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The incidence of CRF during cancer treatment has been reported to range from 25% to 99%, with moderate to severe CRF occurring in 30% to 60% of cases (1). In colorectal cancer survivors, more than one-third continue to suffer from CRF for a year or longer after the end of cancer treatment (3). At present, there are no universally accepted and effective pharmacological treatments for CRF.…”
Section: Introductionmentioning
confidence: 99%
“…18 This review concluded that decreased circulating levels of Trp and a higher kynurenine-to-tryptophan ratio (KTR) were cross-sectionally associated with more fatigue and worse HRQoL among patients with lymphoma, 19 lung cancer, 20 and patients with various types of cancer, including gastrointestinal tumors, hematological malignancy, gynecological neoplasm, and lung cancer. 21 Only limited studies have investigated the involvement of Trp and/or Kyn in cancer-related fatigue and HRQoL specifically in CRC, 22,23 and reported that higher Trp concentrations were associated with less fatigue.…”
Section: Introductionmentioning
confidence: 99%